Assessment of Heavy metals in Sediments, Water and Carias gariepinus from Alau Dam, Borno State Nigeria (Sahel Journal of Life Sciences FUDMA, 2023)
Alau dam attracts commercial fishing and farming activities creating a booming market for individuals involved in the fish and vegetable businesses. The lake having flowed into several towns and villages coupled with the socio-economic activities along its bank received effluents with different concentrations of heavy metals. The study was aimed at assessing the levels of selected heavy metals (Pb, Cd, Cr, As and Hg) concentrations in the sediments, water and Clarias gariepinus from Alau dam, Borno State, Nigeria. Samples were collected bi-weekly for 3 months and analyzed using standards methods. The result of the study indicates that heavy metal concentrations (Pb, Cd and Cr) in the sediments (2.120 ± 0.011, 1.004 ± 0.010 and 0.300 ± 0.010 mg/kg respectively) were all above USEPA permissible limits. The study further shows that exception of Cr (0.011 ± 0.007) all other analyzed metals were above NESREA limits. Additionally, the concentrations of Pb, Cd, Cr, As and Hg in the fish samples (1.020 ± 0.011, 0.940 ± 0.022, 0.001 ± 0.017, 0.010 ± 0.112 and 0.005 ± 0.033 mg/kg respectively) were within the NAFDAC limit. The Non-Cancer Risk (HQ were ˃ 1 in all calculated samples) and Cancer Risks (˃10-3 in all calculated samples) revealed high health risk from ingestion of the C. gariepinus from the study area. Furthermore, the BAF ratio shows Cd ˃ Pb ˃ Hg ˃ As ˃ Cr. The study recommends strict enforcement of NESREA regulations and a continuous monitoring of the levels of heavy metals concentration in the dam.